2004
DOI: 10.1124/jpet.104.068932
|View full text |Cite
|
Sign up to set email alerts
|

A New Poly(ADP-Ribose) Polymerase Inhibitor, FR261529 [2-(4-Chlorophenyl)-5-quinoxalinecarboxamide], Ameliorates Methamphetamine-Induced Dopaminergic Neurotoxicity in Mice

Abstract: Methamphetamine (METH) administration in mice, results in a chronic dopamine (DA) depletion associated with nerve terminal damage, with DA oxidation and generation of reactive oxygen species (ROS) primarily mediating this neurotoxicity. The oxidative stress induced by METH putatively activates nuclear enzyme poly(ADPribose) polymerase (PARP), with excessive PARP activation eventually leading to cell death. In this study, we show that prevention of PARP activation by treatment with FR261529 [2-(4-chlorophenyl)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Brain (occipital cortex) drug levels for the high and low groups are 124 Ϯ 47 (range, 20 -319; median 90) and 10.0 Ϯ 1.3 (range, 2.8 -15.6; median 10) nmol/g tissue, respectively (p Ͻ 0.01, Mann-Whitney U tests). Dopamine levels (previously reported by Wilson et al, 1996 andMoszczynska et al, 2004) Kim et al, 1999;Kita et al, 2000;Wan et al, 2000;Gluck et al, 2001;Flora et al, 2002;Iwashita et al, 2004). Nevertheless, the possibility also has to be considered that chronic drug exposure (e.g., involving tolerance, sensitization) might also have modulated the effects of an acute exposure, as suggested by some animal data (Acikgoz et al, 1998(Acikgoz et al, , 2000.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Brain (occipital cortex) drug levels for the high and low groups are 124 Ϯ 47 (range, 20 -319; median 90) and 10.0 Ϯ 1.3 (range, 2.8 -15.6; median 10) nmol/g tissue, respectively (p Ͻ 0.01, Mann-Whitney U tests). Dopamine levels (previously reported by Wilson et al, 1996 andMoszczynska et al, 2004) Kim et al, 1999;Kita et al, 2000;Wan et al, 2000;Gluck et al, 2001;Flora et al, 2002;Iwashita et al, 2004). Nevertheless, the possibility also has to be considered that chronic drug exposure (e.g., involving tolerance, sensitization) might also have modulated the effects of an acute exposure, as suggested by some animal data (Acikgoz et al, 1998(Acikgoz et al, , 2000.…”
Section: Discussionmentioning
confidence: 97%
“…We hypothesized that, as in most of the experimental animal studies in which MDA or MDA-like thiobarbituric acid reactive substances (TBARS) were reported to be increased in brain of MA-treated rodents (Acikgoz et al, 1998(Acikgoz et al, , 2000Jayanthi et al, 1998;Yamamoto and Zhu, 1998;Kim et al, 1999;Kita et al, 2000;Wan et al, 2000;Gluck et al, 2001;Flora et al, 2002;Iwashita et al, 2004), levels of both oxidative markers would be above-normal in the dopamine-rich caudate nucleus of human MA users but less markedly increased (if at all) in brain areas having very low (frontal and cerebellar cortices) concentrations of dopamine. Our human post mortem data provide additional support to the notion based on animal models that MA can cause oxidative damage in human brain.…”
mentioning
confidence: 99%
“…Down-regulation of PARP-1 might be protective for PD by preventing oxidative stress, suppressing the inflammatory response associated with activated microglia, or by reducing α-synuclein expression level. In fact, inhibition of PARP-1 results in significant neuroprotection in the MPTP mouse model of Parkinson's disease [10]. Considering the interaction between PARP-1 and NACPRep1 polymorphic site upstream of the α-synuclein gene [4], it is tempting to speculate that the association between α-synuclein variants and PD risk has been controversial in the literature [11], probably, at least in part, because analysis of PARP-1 polymorphism has not been simultaneously included.…”
Section: Discussionmentioning
confidence: 98%
“…MPTP is a neurotoxin that causes parkinsonism in humans and animals; mice lacking the PARP gene are dramatically spared from MPTP neurotoxicity [73]. Moreover, PARP inhibitors have been shown to be a valuable neuroprotective tool in models of PD [74,75]. PARP-1 variants are reported to be protective against PD [76].…”
Section: Genomic Factors Associated With Thiamine In Parkinson's Diseasementioning
confidence: 97%